DEVELOPMENT OF ELECTRONIC LEARNING SYSTEMS FOR SPECIAL NEEDS CHILDREN (AUTISM) AT ELEMENTARY SCHOOL LEVEL IN EFFORTS TO INCREASE COGNITIVE INTELLIGENCE - Rulin Swastika; Imam Prasodjo; Daeroby Daeroby (Jurnal TAM (Technology Acceptance Model), 2020)
In an effort to increase cognitive intelligence in children with special needs at the elementary school level, many factors can influence one of the proper learning model specifically for children with autism. In the learning process in the classroom, most of them still use the lecture method, therefore in the learning process students tend to be less interested in the learning process This study aims to develop a learning system using e-learning for children with special needs at the elementary school level using the multimedia to increase cognitive abilities. The research of Learning Management Moodle System is one of the solution that can solve learning problems for students with special needs. Data collection methods used in this study are: observation, interviews, literature study, literature study, questionnaires, and systems development methods. The steps for  systems development method are analyzing data requirements, analyzing process requirements, analyzing software and hardware requirements, analyzing user needs, designing business models, systems designing, systems implementing and system testing. With the existence of an e-learning learning system for children with special needs, it can overcome learning deficiencies in class and students can carry out remote learning anywhere, anytime and repeatedly in a more interactive and fun way, so as to increase student understanding.